1994
DOI: 10.1073/pnas.91.7.2728
|View full text |Cite
|
Sign up to set email alerts
|

Protein S binds to and inhibits factor Xa.

Abstract: Although human protein S binds to human factor Va and inhibits prothrombinase activity, this inhibition is not totally dependent on factor Va. Hence, we investipted possible interaction of protein S with human factor Xa. Factor Xa, dilsopropyiphospho-factor Xa and their biotin derivatives ligand blotted specifically to protein S and protein S ligand blotted specifically to factor X and factor Xa. Biotinylated factors X and Xa bound to immobilized protein S and, reciprocally, protein S bound to immobilized fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
154
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(161 citation statements)
references
References 27 publications
4
154
0
1
Order By: Relevance
“…[9][10][11] In addition, PS might directly limit thrombin generation by binding to and inhibiting factor Xa and FVa in the prothrombinase complex. 12,13 APC-cofactor activity of PS is consistent with the similar clinical manifestations associated with deficiencies in PS and protein C, but is in marked contrast with the weak potentiating effect of PS on APC proteolytic activity in vitro. Indeed, an only approximately 20-fold stimulation of APC-catalyzed cleavage of FVa by PS has been reported in purified systems.…”
Section: Introductionmentioning
confidence: 62%
“…[9][10][11] In addition, PS might directly limit thrombin generation by binding to and inhibiting factor Xa and FVa in the prothrombinase complex. 12,13 APC-cofactor activity of PS is consistent with the similar clinical manifestations associated with deficiencies in PS and protein C, but is in marked contrast with the weak potentiating effect of PS on APC proteolytic activity in vitro. Indeed, an only approximately 20-fold stimulation of APC-catalyzed cleavage of FVa by PS has been reported in purified systems.…”
Section: Introductionmentioning
confidence: 62%
“…It functions as an essential cofactor for activated protein C (aPC) in the degradation of coagulation factors FVa and FVIIIa (1)(2)(3) and thus operates at a central node in the coagulation cascade. In in vitro assays, ProS also binds directly to FVa, FVIIIa, and FXa (4,5), although the extent to which it functions as an aPC-independent anticoagulant in vivo is debated.…”
Section: Introductionmentioning
confidence: 99%
“…Protein S also expresses anticoagulant activity independent of APC by directly inhibiting prothrombin activation [14,15]. Recently, it was reported that protein S stimulates the inhibition of the extrinsic coagulation pathway by TFPI [16].…”
Section: Introductionmentioning
confidence: 99%